2005
DOI: 10.1111/j.1365-2257.2004.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

CA 125 levels in patients with non-Hodgkin lymphoma and other hematologic malignancies

Abstract: Cancer antigen (CA 125) is a glycoprotein commonly used as a tumor marker. In this study, CA 125 levels were measured in 149 patients and 26 healthy control subjects. The study group included 69 non-Hodgkin lymphomas (NHL), 25 Hodgkin disease (HD), 20 acute myelocytic leukemia (AML), 14 chronic lymphocytic leukemia (CLL), 12 chronic myelocytic leukemia (CML), and nine multiple myeloma (MM) patients. CA 125 was elevated in 37 of the patients and in none of the control subjects. Average CA 125 level in NHL patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
3
12
0
9
Order By: Relevance
“…The serum CA125 level in our patient was indeed elevated initially (91 U/mL [reference limits 0-34 U/mL]) but decreased to within normal range after the first cycle of treatment. It has been previously suggested that cytokines such as interleukin (IL)-1β and tumor necrosis factor-α (TNF-α) secreted by myeloma cells might lead to secretion of CA125 by mesothelial cells [21]. Given the extent of peritoneal involvement in our patient; it does seem to confirm the correlation between elevated CA125 level and abdominal involvement.…”
Section: Discussionsupporting
confidence: 66%
“…The serum CA125 level in our patient was indeed elevated initially (91 U/mL [reference limits 0-34 U/mL]) but decreased to within normal range after the first cycle of treatment. It has been previously suggested that cytokines such as interleukin (IL)-1β and tumor necrosis factor-α (TNF-α) secreted by myeloma cells might lead to secretion of CA125 by mesothelial cells [21]. Given the extent of peritoneal involvement in our patient; it does seem to confirm the correlation between elevated CA125 level and abdominal involvement.…”
Section: Discussionsupporting
confidence: 66%
“…However, in benign ovarian diseases it is found to be raised [5,25] [15,25]. The interesting feature of the present study is correlation of CA 125 with clinico-pathological features.…”
Section: Discussionmentioning
confidence: 88%
“…The role of CA 125 in differentiating cancer cases from benign condition is also reported in pelvic lesions and non-Hodgkin lymphomas [14,15].…”
Section: Discussionmentioning
confidence: 95%
“…In NHL patients high levels of CA125 were observed to be correlated to the presence of abdominal and serosal involvement. The exact mechanism of CA125 elevation in these cases is unclear, but it has been proposed that cytokines such as interleukin (IL)-1β and tumor necrosis factor-α (TNF-α) secreted by lymphoma cells might lead to secretion of CA125 by mesothelial cells (Dilek et al, 2005). In our patient, although there were no abdominal involvement and serosal effusion, his CA125 level was extremely high on admission and dramatically decreased to normal limits after chemotherapy and never increased to higher than reference limits again.…”
Section: Discussionmentioning
confidence: 99%